2022
DOI: 10.1109/jstars.2022.3148393
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Spatially Downscaled Solar-Induced Chlorophyll Fluorescence to Monitor Drought Effects on Gross Primary Production in Winter Wheat

Abstract: The impacts of drought on the terrestrial gross primary production (GPP) are the most intense and widespread in all extreme climate events. Solar-induced chlorophyll fluorescence (SIF) is considered as a direct representative of actual vegetation photosynthesis and has better performance in monitoring vegetation conditions than greenness-based vegetation indices (VIs) during drought events. Based on the spatially downscaled SIF (SIFds), VIs and GPP products, we explored the potential of SIFds to monitor drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In contrast, downscaled SIF products have a better spatial resolution (0.05 • ), allowing for better differentiation between grassland and other land use types. Downscaled SIF also has a shorter temporal resolution (8 days), capturing the changes in vegetation due to drought better than other SIF data [32]. Our study area is mainly grassland in the Xilingol League, which is relatively homogeneous and meets the research requirements.…”
Section: Reasons For the Different Performances Of Sif And Vis In Gpp...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, downscaled SIF products have a better spatial resolution (0.05 • ), allowing for better differentiation between grassland and other land use types. Downscaled SIF also has a shorter temporal resolution (8 days), capturing the changes in vegetation due to drought better than other SIF data [32]. Our study area is mainly grassland in the Xilingol League, which is relatively homogeneous and meets the research requirements.…”
Section: Reasons For the Different Performances Of Sif And Vis In Gpp...mentioning
confidence: 99%
“…Chen et al ( 2019) investigated the potential of SIF in monitoring summer maize GPP under drought conditions and found that SIF was able to track spatiotemporal variations in GPP due to drought more effectively than NDVI [31]. Shen et al (2022) explored the capability of SIF in estimating the impact of drought on winter wheat GPP, demonstrating that SIF can accurately quantify GPP losses caused by drought [32]. However, research on the potential of SIF monitoring for grassland ecosystem GPP changes induced by drought is still relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Several models are developed to estimate GPP and mainly they can be grouped as (1) Enzyme kinetic (EK) models 16 , 17 , (2) Empirical models 18 , (3) Solar-induced chlorophyll fluorescence (SIF) models 8 , 19 21 and (4) Light use efficiency (LUE) models 22 , 23 . LUE models are the most preferred approach for use of RS data and have undergone extensive improvements and modifications which add to their accuracy and adaptability to a wide range of conditions 24 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Li and Xiao [25] OCO Various downscaled satellite SIF products have been developed, including SIF* [15], RSIF [16], SIF ______ 005 [17], SIF*new [18], SIFHuMo [19], SIFnet [20], TSIF [21], SDSIF [22], DSIF [23], and others [24]- [32], with applications in examining GPP responses to climate anomalies [33], [34], crop productivity forecasting [28], [35], poverty prediction [36], photosynthesis phenology [37], and vegetation zonality [38]. The existing SIF downscaling studies are summarized in Table I, showcasing the variety of approaches employed for downscaling satellite SIF products.…”
Section: Introductionmentioning
confidence: 99%